Gambaran Penjualan dan Investası Obat Over the Counter Apotek “X” Kelurahan Karang Anyar Kota Tarakan Menggunakan Analısıs ABC Tahun 2022 - Ayu Febianah; Syuhada Syuhada; Benazir Evita Rukaya (Politeknik Kaltara, 2024)
Drug management includes planning drug availability, including type, amount, quality, and quantity, to increase efficiency. One method used in drug planning is ABC or Pareto. This research aims to look at the sales and investment picture of over-the-counter OTC drugs at Pharmacy